Pengaruh Pemberdayaan Masyarakat terhadap Upaya Pengembangan Desa Wisata - Candra Setiawan; Aini Kusniawati (Jurnal Manajemen Bisnis Era Digital, 2024)
Sadananya District implements community-based tourism as an empowerment approach that involves and positions the community as an important actor in the context of a new development paradigm, namely sustainable development (Sustainable Development Paradigm). The purpose of community empowerment itself is basically to improve the knowledge, attitudes, and skills of each individual, so that they have the ability to work and strive independently in order to improve their quality of life. In addition, the purpose of empowerment is to increase the potential of the community to be able to improve the quality of life for all members of the community through self-help activities (Sutarto, 2007: 153). Primary data is obtained raw from the community and still requires further analysis. Qualitative research is to create systematic, factual and accurate observations regarding the facts or characteristics of a particular population or area. Based on the description of the research results and discussions that have been carried out, the researcher can draw conclusions, including development efforts in the Bendasari, Tanjungsari, and Gunungsari Tourism Villages which are carried out through: (a) Human resource development is carried out through training, discussions, and others. (b) Partnership with River Tubing, Taruna Karya, PLN, Resque, and parties engaged in tourism. (c) Village Government Activities, namely holding meetings, discussions, joint sports. (d) Promotion through social media, word of mouth, publications. (e) Festivals or competitions, namely bird singing competitions held at the Bukit Bubulak tourist attraction in Bendasari Village. (f) Fostering Community Organizations by inviting the community to participate in managing Tourism Villages. (e) Cooperation with Universities or colleges in Ciamis Regency and its surroundings.